Pengaruh Persepsi Karyawan Atas Corporate Social Responsibility (CSR) Terhadap Komitmen Organisasi pada PT. Raja Marga Nagan Raya - Indriani, Khaifa; Zhafira, Nabila Hilmy (Regress: Journal of Economics & Management, 2022)
The purpose of this study was to determine whether there is an effect of employee perceptions of CSR on the organizational commitment of PT Raja Marga. The type of method used is quantitative through data collection using a total sampling technique, namely taking data from the entire population of 98 respondents. Data collection using a questionnaire research instrument (questionnaire) with a Likert scale and data analysis through simple regression analysis with SPSS program tools. The results of the analysis show that partially there is a significant influence on employee perceptions of CSRto organizational commitment at PT. Raja Marga by looking at the significance value (sig) is smaller than the probability, namely sig = 0.001 <0.05 and the t value count is greater than t table, tcount 4.754 > ttable 1.987. Coefficient value = 0.191 or 19.1%. This shows that employees' perception of CSR is one of the factors that influence organizational commitment